Introducing e‐learning in a South African Higher Education Institution: Challenges arising from an intervention and possible responses. (20th April 2012) - Bharuthram, Sharita; Kies, Carolynn
<x xml:space="preserve">Abstract</x> Abstract This article draws on research conducted at a tertiary institution in South Africa as part of the redesigning of an English for Educational Development (EED) course to include an e‐learning online discussion component. The subject material used was based on HIV/AIDS topics that students had to debate within an online discussion forum. Framed by the concept of Multiliteracies and the Social Constructivist view of teaching and learning, this study problematizes students' experiences of the online component in an attempt to explore the potential benefits of and challenges in using e‐learning in teaching and learning and the extent to which e‐learning should be adopted into the EED curriculum. The benefits derived and challenges faced by the students and the writers during the implementation of the intervention are presented with the aim of generating further discussions from researchers on national and international levels. This article briefly contextualizes the study by providing some background information, theory and the research process. It then draws on a number of evaluation tools ranging from course evaluations; classroom discussions and observations; reflective notes; as well as minutes of meetings to evaluate both students and writers participation and experiences. Practitioner Notes What is already known about this topic? Advancements in technology make it imperative to include technology into teaching and learning. Using technology can be both rewarding and challenging. Technology contributes to flexible modes of teaching and learning. What this paper adds Provides an understanding of the University context in South Africa and the literacy levels of students entering higher education in South Africa. Discusses the negative impact that a lack of basic language proficiency has on teaching and learning initiatives. While technical skills are important, it is not sufficient for epistemological success. Discusses some specific benefits of and challenges in using an e‐learning discussion forum. This discussion would be useful for practitioners prior to the implementation of e‐learning into the curriculum. Implications for practice and/or policy Care and caution must be exercised in developing institutional policies that recommend e‐learning interventions. Merely providing ongoing e‐learning training for academics is not sufficient. It is imperative that academics are exposed to current literature on the issues that will prevent them falling into "traps, " eg, using e‐learning to replace teacher interaction or making unrealistic demands on students based on the assumption that all student are technologically literate. Consideration must be given to the social context of students as well as the expertise of students prior to adoption of e‐learning into the curriculum. Highlights the importance of using a "scaffolding approach" to develop expertise of students. Stresses the need for Higher Education Institutions to revisit their minimum entrance requirements.